Managing Organizational Change in Science Phylosophy - Sandi Nasrudin Wibowo; Mugi Harsono (Institute of Computer Science (IOCS), 2021)
Today's organizations face changes in the business environment not only from the local environment but also from the international (global) environment. The ability to manage change is one of the key success factors for every company in order to survive and develop. Managing change is a process from identifying the power to change, the power to vote against change to the people responsible for implementing the change. A diagnostic approach will help ensure the competitiveness and performance of the company. These changes require managing the organization in new ways, so that organizational goals can be achieved more effectively in an ever-changing environment. The challenge faced by organizations is the labor market which tends to demand that work be done using human capital. This of course requires the organization to be managed by applying knowledge and improving the capabilities of its human resources. Facing these continuous changes, organizations must be transparent and able to adapt to environmental changes by making the organization a Learning Organization.